Negative plate and secondary battery

By controlling the mass proportion of carbon, silicon and copper elements in the negative electrode sheet of lithium-ion battery, and optimizing the porosity and liquid retention coefficient of the negative electrode sheet, the problem of difficulty in taking into account both energy density and circulation performance in the prior art is solved, and better battery performance is achieved.

CN119812205AActive Publication Date: 2025-04-11ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411804841.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-11
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

When ensuring liquid retention consistency, it is difficult to take into account both energy density and circulation performance.

Method used

By controlling the mass proportion of carbon, silicon and copper elements in the negative electrode sheet, satisfying the relationship of 5%≤Cu/(Si+C)≤30%, combined with the design of porous current collector and negative electrode active material layer, the porosity and liquid retention coefficient of the negative electrode sheet are optimized.

Benefits of technology

It realizes a negative electrode sheet that takes into account both energy density and circulation performance while ensuring consistency of liquid storage, improving the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005178941780000081
    Figure BDA0005178941780000081
  • Figure BDA0005178941780000091
    Figure BDA0005178941780000091
  • Figure BDA0005178941780000101
    Figure BDA0005178941780000101
Patent Text Reader

Abstract

The invention discloses a negative plate and a secondary battery, the negative plate comprises a negative current collector and a negative active material layer coated on at least one surface of the negative current collector, the negative current collector is a porous current collector, the negative active material layer comprises silicon and a carbon material, and in the area of 250 [mu] m * 150 [mu] m, the silicon and the carbon material are uniformly distributed on the surface of the negative current collector. Parameters, represented by EDS scanning, of the negative plate meet the relation that Cu / (Si + C) is larger than or equal to 5% and smaller than or equal to 30%. The mass ratio of carbon, silicon and copper in the negative plate is controlled to meet the relation that Cu / (Si + C) is larger than or equal to 5% and smaller than or equal to 30%, and the porosity and the liquid retention coefficient of the negative plate are controlled to be within the set range, so that the problem that energy density and cycle performance are considered while liquid retention consistency is guaranteed is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of secondary batteries, and in particular to a negative electrode sheet and a secondary battery. Background Art

[0002] At present, lithium-ion batteries are widely used in various digital products and power battery fields due to their high energy density. With the growing demand for fast charging technology in digital products, higher and higher requirements are placed on the energy density and fast charging capacity of lithium-ion batteries. In particular, there are some technical problems that have not yet been fully resolved in the design and function of electrode sheets.

[0003] In the prior art, foam metal foil has attracted widespread attention due to its large surface area, which can improve the electron transfer rate of the electrode. It is also porous and interconnected in the thickness direction of the electrode piece, which can avoid the difference between the AB surfaces of traditional coating, and lithium ions can diffuse freely, thereby improving consistency. However, due to its large thickness, the electrode piece after coating has a large surface density, which may cause problems such as incompatibility with conventional positive or negative electrodes or excessive N / P, resulting in energy density and performance loss.

[0004] In view of these problems, there is an urgent need to develop a negative electrode sheet to solve the problem of liquid retention consistency and the inability to balance energy density and cycle performance. Summary of the invention

[0005] The purpose of the present invention is to provide a negative electrode sheet that can ensure the consistency of liquid retention while taking into account both energy density and cycle performance in view of the shortcomings of the prior art.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector, wherein the negative electrode current collector is a porous current collector, and the negative electrode slurry comprises silicon and carbon materials. Within an area of ​​250 μm*150 μm, the parameters of the negative electrode sheet characterized by EDS scanning satisfy the relationship: 5%≤Cu / (Si+C)≤30%, wherein Cu is the mass proportion of the copper element in the negative electrode sheet, Si is the mass proportion of the silicon element in the negative electrode sheet, and C is the mass proportion of the carbon element in the negative electrode sheet.

[0008] Preferably, the porosity of the negative electrode sheet is i, and i satisfies the relationship: 30%≤i≤65%;

[0009] And / or, the content of Si element in the negative electrode sheet is 3-55%, the content of C element is 45-96%, and the content of O element is 0-1%.

[0010] Preferably, the pore size d of the porous current collector satisfies the relationship: 10 μm≤d≤400 μm.

[0011] Preferably, the porous current collector is one of copper mesh, foam copper, three-dimensional copper foil, or a combination of two or more of them.

[0012] Preferably, the negative electrode active material layer is made of negative electrode slurry, and the negative electrode active material layer, negative electrode slurry and copper foam satisfy the following relationship: x=a*z*10000 / (ρ*h*m*y); z=h / D; wherein x is the negative electrode slurry filling rate of the copper foam pores, a is the surface density of the negative electrode sheet, ρ is the density of the negative electrode slurry, D is the thickness of the copper foam before rolling, h is the thickness of the copper foam after rolling, m is the solid content of the negative electrode slurry, and y is the porosity of the copper foam;

[0013] The thickness D of the copper foam before rolling satisfies the relationship: 50 μm≤D≤1000 μm, and the porosity y of the copper foam satisfies the relationship: 50%≤y≤99%.

[0014] Preferably, the thickness h of the copper foam after rolling, the negative electrode slurry filling rate x of the copper foam pores and the thickness D of the copper foam before rolling satisfy the relationship: x<h / D+11%.

[0015] The thickness h of the foam copper after rolling satisfies the relationship: 35 μm≤h≤200 μm.

[0016] Preferably, the pore size d of the foam copper before rolling satisfies the relationship: 40 μm≤d≤400 μm.

[0017] Preferably, the value of z is 20%-90%.

[0018] Preferably, the surface density a of the negative electrode sheet satisfies the relationship: 2.4*10 -3 g / cm 2 ≤a≤14.5*10 -3 g / cm 2 .

[0019] Preferably, the solid content m of the negative electrode slurry satisfies the relationship: 25%≤m≤60%.

[0020] In addition, the present invention also provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, wherein the negative electrode sheet is the above-mentioned negative electrode sheet.

[0021] Compared with the prior art, the beneficial effect of the present invention is that the present invention controls the mass proportion of carbon, silicon and copper elements in the negative electrode sheet to satisfy the relationship: 5%≤Cu / (Si+C)≤30%, which is used to control the porosity and liquid retention coefficient of the negative electrode sheet within a set range to ensure the consistency of liquid retention while taking into account both energy density and cycle performance. DETAILED DESCRIPTION

[0022] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.

[0023] According to the first aspect of the present application, the present application aims to provide a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector, the negative electrode current collector is a porous current collector, the negative electrode active material layer comprises silicon and carbon materials, and within an area of ​​250 μm*150 μm, the parameters of the negative electrode sheet characterized by EDS scanning satisfy the relationship: 5%≤Cu / (Si+C)≤30%, wherein Cu is the mass proportion of the copper element in the negative electrode sheet, Si is the mass proportion of the silicon element in the negative electrode sheet, and C is the mass proportion of the carbon element in the negative electrode sheet; for example, Cu / (Si+C) can be 5%, 10%, 15%, 20%, 25% or 30%.

[0024] Among them, when the proportion of Cu is low, the porosity decreases after rolling, the ability to store electrolyte decreases, and the cycle performance is greatly deteriorated; when the proportion of Cu increases, the porosity of the electrode increases after rolling, the ability to store electrolyte increases, and the cycle performance improves; but if the proportion of Cu is too high, the porosity of the electrode will be too high, and the cycle performance of the electrode will be greatly reduced due to excessive liquid absorption. By controlling the mass proportion of carbon, silicon and copper elements in the negative electrode to meet the relationship: 5% ≤ Cu / (Si+C) ≤ 30%, it is used to control the porosity and liquid retention coefficient of the negative electrode within the set range to ensure the consistency of liquid retention while taking into account energy density and cycle performance.

[0025] In some embodiments, the porosity of the negative electrode sheet is i, and i satisfies the relationship: 30%≤i≤65%, for example, it can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%. When i is too small, the porosity of the electrode sheet is too low, and the ability to store electrolyte decreases. During the battery cycle, the electrolyte is easily dried up, resulting in an increase in ion tortuosity and disconnection of the ion conductive path, thereby greatly reducing the cycle performance. When i is too large, the porosity of the electrode sheet is too large, and the ability to store electrolyte increases. Due to excessive liquid absorption, the electrode sheet has too much electrolyte and more side reactions in a high temperature environment, resulting in a significant reduction in high temperature storage performance.

[0026] In some embodiments, the liquid retention coefficient of the negative electrode sheet is b, and b satisfies the relationship: 1.1g / Ah≤b≤1.45g / Ah, for example, it can be 1.1g / Ah, 1.15g / Ah, 1.2g / Ah, 1.25g / Ah, 1.3g / Ah, 1.35g / Ah, 1.4g / Ah, 1.45g / Ah. When b is too small, it will limit the transmission of lithium ions between the positive and negative electrodes, increase the internal resistance of the battery, and reduce its cycle stability; when b is too large, it may cause excess electrolyte to decompose during the charge and discharge process, generate gas, and affect the safety and cycle stability of the battery.

[0027] And / or, the content of Si element in the negative electrode sheet is 3-55%, for example, it can be 3%, 5%, 10%, 20%, 30%, 40%, 50%, 55%; the content of C element is 45-96%, for example, it can be 45%, 55%, 65%, 75%, 85%, 95%, 96%; the content of O element is 0-1%, for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%.

[0028] Among them, a small amount of oxygen element exists in the active material graphite in the negative electrode sheet.

[0029] In some embodiments, the pore size d of the porous current collector satisfies the relationship: 10 μm ≤ d ≤ 400 μm, preferably, the pore size d of the porous current collector satisfies the relationship: 10 μm ≤ d ≤ 200 μm, for example, it can be 10 μm, 50 μm, 100 μm, 150 μm, 200 μm, 300 μm, 400 μm.

[0030] In some embodiments, the porous current collector is a copper mesh, a foam copper, a three-dimensional copper foil, or a combination of two or more thereof.

[0031] In some embodiments, the negative electrode active material layer is made of negative electrode slurry, and the negative electrode sheet, negative electrode slurry and copper foam satisfy the following relationship: x=a*z*10000 / (ρ*h*m*y); z=h / D;

[0032] Wherein, x is the negative electrode slurry filling rate of the foam copper pores, a is the surface density of the negative electrode sheet, ρ is the density of the negative electrode slurry, D is the thickness of the foam copper before rolling, h is the thickness of the foam copper after rolling, m is the solid content of the negative electrode slurry, and y is the porosity of the foam copper;

[0033] When this relationship is satisfied, the upper limit problem of the super-positive electrode adaptation coating window caused by the thick foil thickness of the foam copper negative electrode sheet can be solved, that is, the energy density of the battery can be guaranteed while improving the rate performance.

[0034] Among them, controlling 50μm≤D≤1000μm can ensure that the slurry penetrates into the pores to avoid excessive surface density, and controlling 50%≤y≤99% can ensure the battery energy density while avoiding the reduction of electrochemical performance.

[0035] The thickness D of the copper foam before rolling satisfies the relationship: 50 μm ≤ D ≤ 1000 μm, and the porosity y of the copper foam satisfies the relationship: 50% ≤ y ≤ 99%. The value of D can be, for example, 50 μm, 150 μm, 250 μm, 350 μm, 450 μm, 550 μm, 650 μm, 750 μm, 850 μm, 950 μm, 1000 μm.

[0036] When the thickness D of the copper foam before rolling is less than 50μm, large active particles are easily squeezed out of the gap or crushed, resulting in a decrease in the overall performance of the electrode, leading to a decrease in the rate and cycle performance of the battery cell; when the thickness D of the copper foam before rolling is greater than 1000μm, the battery energy density decreases due to the large proportion of inactive materials. The value of y can be, for example, 50%, 60%, 70%, 80%, 90%, and 99%. When the porosity y of the copper foam is less than 50%, the energy density will decrease; when the porosity y of the copper foam is greater than 99%, the conductivity of electrons will decrease due to the low proportion of copper foil, causing the battery's ohmic internal resistance to increase, thereby reducing the electrochemical performance.

[0037] In some embodiments, the thickness h of the copper foam after rolling, the negative electrode slurry filling rate x of the copper foam pores, and the thickness D of the copper foam before rolling satisfy the relationship: x<h / D+11%. When the three satisfy this relationship, the porosity (1-x) can be reserved before rolling so that the active material is evenly present in the pores of the foil during the rolling process of the electrode sheet without the phenomenon of bulging edge after rolling.

[0038] In some embodiments, the thickness h of the copper foam after rolling satisfies the relationship: 35 μm≤h≤200 μm, for example, it can be 35 μm, 50 μm, 100 μm, 135 μm, 150 μm, or 200 μm.

[0039] In some embodiments, the value of z is 20%-90%, for example, it can be 20%, 30%, 40%, 50%, 60%, 70%, 80%, or 90%.

[0040] In some embodiments, the surface density a of the negative electrode sheet satisfies the relationship: 2.4*10 -3 g / cm 2 ≤a≤14.5*10 -3 g / cm 2 , for example, it can be 2.4*10 -3 g / cm 2 , 2.5*10 -3 g / cm 2 , 5*10-3 g / cm 2 , 6*10 -3 g / cm 2 ,8*10 -3 g / cm 2 , 10*10 -3 g / cm 2 , 12*10 -3 g / cm 2 、14.5*10 -3 g / cm 2 .

[0041] In some embodiments, the solid content m of the negative electrode slurry satisfies the relationship: 25%≤m≤60%, for example, it can be 25%, 30%, 35%, 40%, 45%, 50%, or 60%.

[0042] According to a second aspect of the present application, the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator separated between the positive electrode sheet and the negative electrode sheet, wherein the negative electrode sheet is the negative electrode sheet mentioned above.

[0043] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material. The positive electrode active material may include but is not limited to a chemical formula such as Li a Ni x Co y M z O 2-b N b (where 0.95≤a≤1.2, x>0, y≥0, z≥0, and x+y+z=1, 0≤b≤1, M is selected from a combination of one or more of Mn and Al, and N is selected from a combination of one or more of F, P, and S), the positive electrode active material may also be, but is not limited to, LiCoO2, LiNiO2, LiVO2, LiCrO2, LiMn2O4, LiCoMnO4, Li2NiMn3O8, LiNi 0.5 Mn 1.5O4, LiCoPO4, LiMnPO4, LiFePO4, LiNiPO4, LiCoFSO4, CuS2, FeS2, MoS2, NiS, TiS2, etc. The positive active material may also be modified. The method of modifying the positive active material should be known to those skilled in the art. For example, the positive active material may be modified by coating, doping, etc. The material used for the modification may include but is not limited to a combination of one or more of Al, B, P, Zr, Si, Ti, Ge, Sn, Mg, Ce, W, etc. The positive current collector is usually a structure or part for collecting current. The positive current collector may be various materials suitable for use as a positive current collector for lithium-ion batteries in the art. For example, the positive current collector may include but is not limited to metal foil, etc., and more specifically may include but is not limited to aluminum foil, etc.

[0044] The separator can be any material suitable for secondary battery separators in the art, for example, it can be a combination of one or more of, but not limited to, polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fibers.

[0045] The secondary battery also includes an electrolyte, which includes an organic solvent, an electrolyte lithium salt and an additive. Among them, the electrolyte lithium salt can be LiPF6 and / or LiBOB used in high-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, and LiPF6 used in low-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, LiPF6, and LiTFSI used in anti-overcharge electrolytes; it can also be at least one of LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2. The organic solvent can be a cyclic carbonate, including PC and EC; it can also be a chain carbonate, including DFC, DMC, or EMC; it can also be a carboxylic acid ester, including MF, MA, EA, MP, etc. The additives include but are not limited to at least one of film-forming additives, conductive additives, flame retardant additives, anti-overcharge additives, additives for controlling the content of H2O and HF in the electrolyte, additives for improving low-temperature performance, and multifunctional additives.

[0046] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.

[0047] Example 1

[0048] 1) Preparation of negative electrode sheet:

[0049] The negative electrode active material silicon-based active material is mixed with carbon active material, conductive agent carbon black, CNT, and binder PAA in a mass ratio of 80:9:1:10, wherein the mass ratio of silicon-based active material to carbon active material in the negative electrode active material is 7.5:92.5, solvent water is added, and the system is stirred under the action of a vacuum stirrer until the system is uniform to obtain a negative electrode slurry, the slurry is poured into a scraper groove, and the surface of the foam copper is scraped at a speed of 33 mm / s on an automatic coating machine, and then the negative electrode sheet is obtained by roller pressing and baking.

[0050] Among them, the porosity i of the negative electrode sheet is 45%, the liquid retention coefficient b of the negative electrode sheet is 1.35, and the surface density a of the negative electrode sheet is 0.00896 g / cm 2 The density of the negative electrode slurry is 1.39 g / cm 3 The solid content m of the negative electrode slurry is 49.89%, the porosity y of the foam copper is 97.6%, the pore size d of the foam copper is 70μm, the thickness D of the foam copper before rolling is 184μm, the thickness h of the foam copper after rolling is 114μm, and the negative electrode slurry filling rate x of the foam copper pores is 71.95%.

[0051] Among them, within an area of ​​250 μm*150 μm, the parameter Cu / (Si+C) of the negative electrode sheet characterized by EDS scanning is 25%.

[0052] 2) Preparation of positive electrode:

[0053] Lithium cobalt oxide, conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 97:2:1, solvent NMP is added, and the system is stirred until the system is uniform under the action of a vacuum mixer to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0054] 3) Preparation of isolation membrane:

[0055] The base film of the isolation membrane adopts a polyethylene base film, and a first coating of vinylidene fluoride and ceramic particles and a second coating of styrene butadiene rubber and ceramic particles are coated on both sides of the membrane respectively to make the membrane.

[0056] 4) Preparation of electrolyte:

[0057] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a lithium salt concentration of 1 mol / L.

[0058] 5) Battery preparation:

[0059] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare cell; the bare cell is placed in an outer packaging shell, and after drying, an electrolyte is injected, and a lithium-ion battery is obtained through vacuum packaging, standing, forming, shaping, and other processes. Among them, the preparation methods of Examples 2-9 and Comparative Examples 1-4 are the same as the preparation method of Example 1, except for the parameters of the negative electrode sheet, as shown in Table 1-2 below.

[0060] Table 1

[0061]

[0062] Table 2

[0063]

[0064] Performance test: The lithium-ion batteries obtained in the examples and comparative examples were subjected to the following tests respectively. The test results are shown in Table 3 below.

[0065] (1) Element content test: Within an area of ​​250um*150um, the distribution and weight ratio of each element are obtained by scanning the electrode EDS and analyzing the EDS energy spectrum.

[0066] (2) Pole plate porosity test: Gas permeation method, which calculates the porosity by injecting nitrogen gas into the pores of the battery pole plate and then measuring the pressure change.

[0067] (3) Liquid retention coefficient test: electrolyte weight / cell capacity after volume division.

[0068] (4) Energy density test: 0.2C capacity of battery cell*platform voltage / volume of battery cell, unit: (Wh / L).

[0069] (5) Discharge retention rate test: The charging method is 0.5C constant current and constant voltage charging to 4.5V, the cut-off current is 0.05C, and the 0.2C discharge capacity Cap0 is used as the benchmark. 3C discharge is performed to obtain Cap1, and the capacity retention rate is Cap| / Cap0.

[0070] (6) Cycle test: Charge to 4.5 V at 1 C constant current and constant voltage, with a cut-off current of 0.05 C, and discharge to 3.0 V at 0.2 C until the capacity retention rate reaches 80% and the cycle is completed.

[0071] (7) High-temperature storage thickness expansion rate test: Take the thickness H0 of the battery cell in the fully charged state before cycling as the reference, place it in a 60°C environment for 21 days, take it out and place it at room temperature for 2 hours, measure the thickness H1, and the thickness expansion rate = H1 / H0-1.

[0072] (8)极差 of liquid retention capacity: After vacuum drying for a period of time, electrolyte is injected into the battery, and the initial injection volume is recorded. After a period of electrolyte infiltration treatment, the excess electrolyte inside the battery is pumped out, and the electrolyte pumping volume is recorded. Therefore, the liquid retention capacity = injection volume - electrolyte pumping volume. Take 100 batteries as the number of samples, and calculate the range of the liquid retention capacity obtained to get the range of the liquid retention capacity.

[0073] Table 3

[0074]

[0075]

[0076] From the data comparison between Example 1 and Comparative Examples 1-4, when Cu / (Si + C) < 5%, the porosity i of the electrode sheet < 30%, and the liquid retention coefficient m (g / Ah), m ≤ 1.1. Since the proportion of Cu is low and the entire electrode sheet skeleton is determined by the material area, it will cause the porosity to decrease after rolling under the same compaction of the electrode sheet, and the ability to store electrolyte will decline. The cycle storage performance of the battery made will be greatly reduced.

[0077] When the proportion of Cu is too high, that is, Cu / (Si + C) > 30%, it will cause the electrode sheet to be too hard and the porosity after rolling to be too high. As a result, the electrode sheet absorbs too much liquid, the liquid retention capacity is too high, and side reactions increase, affecting the high-temperature storage performance. Moreover, due to the increase in the proportion of Cu, the exposed part of the electrode sheet has an uneven exposed area of the copper foil. As Cu / (Si + C) increases, the unevenness of the exposed area of Cu becomes higher. Due to the action of the surface tension of the copper foil on the electrolyte, the ability to store electrolyte increases, but the liquid retention consistency (range of liquid retention capacity) is worse, and the cycle performance is greatly reduced.

[0078] When the proportion of Cu is in the range of 5% ≤ Cu / (Si + C) ≤ 30%, since the proportion of Cu increases and the entire electrode sheet skeleton is determined by Cu, the porosity i and the liquid retention coefficient b of the electrode sheet can satisfy the following relational expressions: 30% ≤ i ≤ 65%, 1.1 ≤ b ≤ 1.45. Therefore, the porosity of the electrode sheet increases after rolling under the same compaction, the ability of the electrode sheet to store electrolyte increases, and the liquid retention consistency within this range is better. When made into a battery, it takes into account both the liquid retention consistency, energy density, and long cycle performance.

[0079] From the data comparison between Examples 1-9 and Example 5 among them, when x < z + 11%, the porosity (1 - x) can be reserved before rolling so that the active material is evenly present in the pores of the foil during the rolling process of the electrode sheet without the phenomenon of edge bulging after rolling; controlling the partial filling of the voids by the slurry, that is, x < 100%, is suitable for the positive electrode to have coatable performance and be assembled into a battery.

[0080] When the slurry filling rate x≤90%, the energy density increases as x increases, and the rate performance is attenuated. Therefore, it is necessary to take into account both the energy density and the rate performance (3C discharge retention rate>90%), and the two are balanced. In Example 5, due to the high slurry filling amount, a slight bulging edge appears, and the rate performance is attenuated, but because the relationship 5%≤Cu / (Si+C)≤30% is satisfied, the performance deterioration is not serious.

[0081] From the data comparison of Examples 1-9, it can be obtained that when the pore size is 10μm≤d≤400μm, the slurry is in good contact with the foil and the high-rate discharge polarization is low. When the pore size is greater than 400μm, the slurry enters the pores, causing the surface density to be too high, local cracks will appear during the drying process, and the rate performance will be reduced.

[0082] From the data comparison of Example 1 and Comparative Examples 1-2, it can be obtained that when the porosity y is less than 50%, the energy density decreases, and when y>99%, the rate performance is reduced due to the low proportion of copper foil, which reduces the ability to conduct electrons.

[0083] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A negative electrode sheet, characterized in that: It includes a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector, wherein the negative electrode current collector is a porous current collector, and the negative electrode active material layer includes silicon and carbon materials. Within an area of ​​250 μm*150 μm, the parameters of the negative electrode sheet characterized by EDS scanning satisfy the relationship: 5%≤Cu / (Si+C)≤30%, wherein Cu is the mass proportion of the copper element in the negative electrode sheet, Si is the mass proportion of the silicon element in the negative electrode sheet, and C is the mass proportion of the carbon element in the negative electrode sheet.

2. The negative electrode sheet according to claim 1, characterized in that: The porosity of the negative electrode sheet is i, where i satisfies the relationship: 30% <i<65%; And / or, the content of Si element in the negative electrode sheet is 3-55%, the content of C element is 45-96%, and the content of O element is 0-1%.

3. The negative electrode sheet according to claim 1, characterized in that: The pore size d of the porous current collector satisfies the relationship: 10 μm≤d≤400 μm.

4. The negative electrode sheet according to claim 1, characterized in that: The porous current collector is one of copper mesh, foam copper, and three-dimensional copper foil, or a combination of two or more of them.

5. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The negative electrode active material layer is made of negative electrode slurry, and the negative electrode active material layer, negative electrode slurry and foam copper satisfy the following relationship: x=a*z*10000 / (ρ*h*m*y); z=h / D; Wherein, x is the negative electrode slurry filling rate of the foam copper pores, a is the surface density of the negative electrode sheet, ρ is the density of the negative electrode slurry, D is the thickness of the foam copper before rolling, h is the thickness of the foam copper after rolling, m is the solid content of the negative electrode slurry, and y is the porosity of the foam copper; The thickness D of the copper foam before rolling satisfies the relationship: 50 μm≤D≤1000 μm, and the porosity y of the copper foam satisfies the relationship: 50%≤y≤99%.

6. The negative electrode sheet according to claim 5, characterized in that: The thickness h of the copper foam after rolling, the negative electrode slurry filling rate x of the copper foam pores and the thickness D of the copper foam before rolling satisfy the relationship: x≤h / D+11%.

7. The negative electrode sheet according to claim 5, characterized in that: The thickness h of the foam copper after rolling satisfies the relationship: 35 μm≤h≤200 μm.

8. The negative electrode sheet according to claim 5, characterized in that: The value of z is 20%-90%; and / or the surface density a of the negative electrode sheet satisfies the relationship: 2.4*10 -3 g / cm 2 ≤a≤14.5*10 -3 g / cm 2 .

9. The negative electrode sheet according to claim 4, characterized in that: The solid content m of the negative electrode slurry satisfies the relationship: 25%≤m≤60%.

10. A secondary battery, characterized in that: A negative electrode sheet comprising any one of claims 1 to 9.

Citation Information

Patent Citations

  • Negative plate and lithium ion battery comprising same

    CN111916753A

  • Porous silicon-carbon composite material and preparation method and application thereof

    CN114709386A

  • Composite particles, negative electrode mixture layer, and lithium ion secondary battery

    CN117321797A

  • Preparation method of negative pole piece and secondary battery

    CN117410435A

  • Electrochemical device and electronic apparatus

    CN117977004A